Probiotic lactic acid bacteria promote anti-tumor immunity through enhanced major histocompatibility complex class I-restricted antigen presentation machinery in dendritic cells - Saito, Suguru; Okuno, Alato; Peng, Zhenzi; Cao, Duo-Yao; Tsuji, Noriko M. (Frontiers in Immunology, 2024)
Lactic acid bacteria (LAB) possess the ability to argument T cell activity through functional modification of antigen presenting cells (APCs), such as dendritic cells (DCs) and macrophages.We invited Dr. Tusji for co-corresponding author to revise. All authors have agreed this change. We also changed the author positions following the contribution in the revise. Nevertheless, the precise mechanism underlying LAB-induced enhancement of antigen presentation in APCs remains incompletely understood. To address this question, we investigated the detailed mechanism underlying the enhancement of major histocompatibility complex (MHC) class I-restricted antigen presentation in DCs using a probiotic strain known as Lactococcus lactis subsp. Cremoris C60. We found that Heat-killed-C60 (HK-C60) facilitated the processing and presentation of ovalbumin (OVA)peptide antigen OVA257-264 (SIINFEKL) via H-2K b in bone marrow-derived dendritic cells (BMDCs), leading to increased generation of effector CD8+ T cells in vitro and in vivo. We also revealed that HK-C60 stimulation augmented the activity of 20S immunoproteasome (20SI) in BMDCs, thereby enhancing the MHC class I-restricted antigen presentation machinery. Furthermore, we assessed the impact of HK-C60 on CD8+ T cell activation in an OVA-expressing B16-F10 murine melanoma model. Oral administration of HK-C60 significantly attenuated tumor growth compared to control treatment. Enhanced Ag processing and presentation machinery in DCs from both Peyer's Patches (PPs) and lymph nodes (LNs) resulted in an increased tumor antigen specific CD8+ T cells. These findings shed new light on the role of LAB in MHC class I antigen presentation and activation of CD8+ T cells through functional modification of DCs.